Educational Policies Matter: How Schooling Strategies Influence Refugee Adolescents' School Participation in Lower Secondary Education in Germany - Will, Gisela; Becker, Regina; Winkler, Oliver (Frontiers in Sociology, 2022)
This article investigates the educational participation of refugee adolescents in Germany as a main European destination country of refugee migration. Opportunities and restrictions for school participation vary not only across countries–, but in the case of the Federal Republic of Germany, also within countries. The influence of different regional educational policies on refugees’ educational participation and the extent to which they limit or enable individual agency, are however, widely understudied. We thus aim to analyze how different regional educational policies within Germany influence refugee students’ educational participation regarding four central indicators: the duration until school enrollment, the type of class attended (newcomer versus regular class), the type of school attended, and whether they are enrolled in settings appropriate for their age. We rely on a theoretical model which sees educational decisions as the result of rational cost-benefit calculations. The individual educational investments depend on individual motivations and resources within a given opportunity structure. We integrate the legal regulations via the opportunity structures into the theoretical model. Our analyses are based on data from 2,415 adolescents who were interviewed in the “ReGES – Refugees in the German Educational System” study. Our results show significant correlations between different regional educational policies and the four domains of educational participation. These effects remain stable when considering family and individual resources, as well as further control variables that previous research on social and ethnic educational inequality has shown to be relevant. Family and individual resources only partially influence educational participation. This indicates that refugee students and their parents have only limited options for action concerning their educational participation. Thus, our study shows that educational policies in fact matter: the assignment to a federal state plays a significant role in determining the duration until school enrollment, whether one is placed to a grade level age-appropriately, and whether one attends a newcomer class. Most significantly, legal regulations strongly influence refugees’ chances of attending a higher school track (Gymnasium). Due to the low permeability of the German education system, this creates path dependencies for the further education and career paths of new immigrant students.